The CAADP 2020 biennial review: Why many countries are off-track - Benin, Samuel (International Food Policy Research Institute, 2020)
This note analyzes the trajectory of the benchmark and its implications for the effort required of countries to remain on-track or get on-track toward achieving the goals and targets of the Malabo Declaration by 2025. It also analyzes the change in the overall score obtained by different countries between the 2018 and 2020 BRs by decomposing the contribution of different indictors to the change. This helps to explain why fewer countries were on-track in the 2020 BR compared to the 2018 BR. The note concludes with a look at the potential challenges countries may face, most notably those brought on by the COVID-19 pandemic, and prospects for them to remain or get on-track in future BRs.